PENINGKATAN KUALITAS KEHIDUPAN MASYARAKAT DESA TEGALJATI BERBASIS KKN TEMATIK POSDAYA MASJID - Miftahus Salam (Institut Agama Islam Tribakti Kediri, 2022)
This article aims to provide an overview regarding improving the quality of life of the people of Tegaljati Village in KKN activities with the theme POSDAYA Mosque. Where Posdaya aims to help empower families and communities through religious and social development. This activity uses the ABCD approach with operational definitions of mapping and analysis related to Problem Based Approach, Need Based Approach, Right Based Approach, Asset Based Approach. the result is that there are three focus activities namely the development of the creative economy, religious development, education improvement, and fostering the younger generation. In the field of creative economic development that is being carried out by d is entrepreneurial innovation from aquatic plants, namely Arnong. The field of religious development carried out by the team is an increase in religious activities. One of the forms is the revitalization of mosque activities such as the congregational prayer movement, revitalizing the mosque with religious activities, as well as deliberations to improve the quality of life for the people of Tegaljati. The field of education that is being carried out is learning assistance for PAUD, MI, MTs, and MA students. The area of ​​coaching the younger generation that is being carried out is the re-establishment of the Remas.